Сучасні реалії трудової міграції українців до Польщі - Карпенко, А. В.; Засоріна, Г. В.; Засорина, А. В.; Karpenko, А.; Zasorina, Н. (ЦНТУ, 2018)
В статті розглянуто суть та динаміку трудової міграції українців до Польщі. Визначено структуру мігрантів за сферою діяльності та часові межі перебування мігрантів в Польщі. Виконане оцінювання впливу сучасних тенденцій міграційних процесів на ринок праці не тільки в Україні, але і в Польщі. Досліджено чинники та негативні наслідки зовнішньої трудової міграції. На основі статистичної інформації розроблені заходи щодо зменшення міграційних потоків та покращення міграційної політики в сучасних умовах. В статье рассмотренасуть и динамика трудовой миграции украинцев в Польшу. Определена структура мигрантов по сфере деятельности и временные рамки пребывания мигрантовв Польше. Выполнена оценка влияния современных тенденций миграционных процессов на рынок труда не только в Украине, но и в Польше. Исследованы причины и негативные последствия внешней трудовой миграции. На основе статистической информации разработаны мероприятия по уменьшению миграционных потоков и улучшению миграционной политики в современных условиях. For today in Ukraine is observing the mass movement of population for work to others countries. It is caused by the row of negative internal factors: economic crisis, political instability, low level of life, desire to self-realization and ect. However, statistical information that is given by government organs doesn’t represent the real state of situation. Accordingly from the side of government organs of power there isn’t the substantial reacting for reduction of negative consequences. For the time being Ukrainian labor migrants are going to work to Germany, Russia, Czech Republic and other countries, but the major migration stream is directed to Poland. Therefore it is very important to investigate the modern tendencies of migratory streams of Ukrainians to Poland and offer measures for to stay and reduction of exodus of population from Ukraine. In the article are considered dynamics and methods of employment of Ukrainians to Poland. The structure of migrants is certain of sphere of activity and are educed the most needed professions for Ukrainians by the Polish employers. There are certain the temporal borders of staying migrants in Poland and their reasons of departure: short-term migrants (earnings of money are for opening their own business), long-term migrants (desire to remain to live in other country). The evaluation of influence of modern tendencies of migratory processes is executed not only to the home market of labor but also to Poland. There are exposed the basic factors and negative consequences of external labor migration. On the basis of statistical information and available in Ukraine legal base that regulates migration, reasonable measures are worked out in relation to the improvement of home migratory politics in modern crisis position with the aim of reduction of migratory streams. For reduction of migratory processes it is necessary to use administrative instruments and provide to work socio-economic mechanism. It is necessary to pay attention to removal and prevention of available causes and effects of labor migration through the improvement of current legislation, introduction of the effective system monitoring of migrants.
Современные реалии трудовой миграции украинцев в Польшу
Modern Realities of Ukrainians Labor Migration to Poland
Keywords: міграція; трудова міграція; зовнішня трудова міграція; нелегальна міграція; міграційна політика; миграция; трудовая миграция; внешняя трудовая миграция; нелегальная миграция; миграционная политика; migration; labor migration; external labor migration; illegal migration; migration policy